Contact angle hysteresis and sliding angle of commercial hydrophobic materials for electrowetting actuating surface / M. Z. Yaacob and E. N. A. Latip - Yaacob, M. Z.; A. Latip, E. N. (UiTM Press, 2024)
Hydrophobic materials are one of the main components in electrowetting-on-dielectric (EWOD) devices, acting as the actuating surface upon which droplets move. EWOD technology has been extensively utilised as a platform for particle detection due to its versatility, simple design, and minimal waste. However, the technology could be more widely adopted if the materials and fabrication costs could be reduced. This study presents an investigation into two off-the-shelf hydrophobic materials as alternatives to conventional materials for the actuating surface component of the device. The surfaces were prepared using two different deposition methods, which were spin coating and spray coating. For each method, samples with two thicknesses were prepared, consisting of one layer and two layers. The contact angle hysteresis and sliding angle of the commercial hydrophobic surfaces were measured. One of the surfaces exhibited good performance with a contact angle hysteresis and sliding angles of 28° and 34°, respectively. These promising findings suggest the potential use of commercial hydrophobic materials for the future development of disposable and low-cost EWOD devices.